Assessing University Students’ Critical Thinking Skill by Using the TOEFL ITP Reading Test - Rentauli Mariah Silalahi (Bina Nusantara University, 2017)
This is a qualitative study trying to find out the students’ ability in applying the critical thinking skill while doing the TOEFL ITP reading test. The student participants were 140 university students in one of the private universities in Indonesia. In order to find out the answer, this research was firstly done by looking at the relationship of critical thinking and reading comprehension skill and investigating the level of students’ reading ability by contrasting their reading score to the Common European Framework of Reference for Languages (CEFR). The study found out that there was an inseparable connection between the students’ critical thinking skill and reading competence and that majority of the student participants were very weak in critical thinking and reading competence skills and so placed at the bottom level of the CEFR.